Recent advances in perovskite oxides for anion-intercalation supercapacitor: A review - Nan, Hao-shan; Hu, Xiao-ying; Tian, Hong-wei (Materials science in semiconductor processing, 2019)
Recently, perovskites have been widely studied as functional materials. Significant attention was paid to the perovskites as an anode material for supercapacitor when the charge storage mechanism of the oxygen-anion-intercalation was proposed. This review summarized the anion-intercalation mechanism and the factors which impact the electrochemical performance of electrodes by researching previous studies on perovskite materials for supercapacitors. Moreover, the issues and the focus of the previous studies have also been discussed herein. The guidelines for the design of perovskite material for supercapacitor were also presented, which is beneficial to the further study of perovskite materials for supercapacitors.